EUROPEAN ENERGY SECURITY AND THE BALKANS: A BATTLEGROUND FOR THE U.S.-RUSSIA STRUGGLE FOR THE GEOSTRATEGIC CONTROL OF EURASIA - (Thrassy) N. MARKETOS, Thrassyvoulos (CENTRAL ASIA AND THE CAUCASUS, 2008)
Europe’s natural gas demand is projected to increase substantially in the future. Even un-der conservative scenarios, the demand for importing natural gas to the EU will double from 200 billion cubic meters (bcm) per annum in 2002 to 400 bcm by 2030, with total demand rising from 400 bcm to up to 600 bcm in same period.1 The greater portion of this increase is likely to come from gas producing countries of Eurasia. Indeed, significant untapped production capacity likely to emerge in Europe’s neighborhood is mainly located in Russia and the Caspian Sea basin—ad-joining the Wider Black Sea region. To transport these energy resources in Europe, of course, requires the building of new transportation networks. Yet unless such alternative delivery options are constructed to bring natural gas from fields in Azerbaijan, Turkmenistan and Kazakhstan to Europe, Russia is likely to fill the vacuum by controlling the transportation of this region’s gas—using its monopoly position in Central Asia to buy gas cheaply and using its monopoly of supply in Europe to sell gas at several times the price to Europe. The Kremlin has been using Russia’s recently acquired economic might, by virtue of the high price of oil and unprecedented demand for natural gas, to pursue one of its primary foreign policy goals: to become the world’s primary supplier of energy resources. To this end, it keeps a tight grip on purchasing and transporting of the oil and gas resources of the former Soviet Un-ion republics. The tragic incidents of 9/11 and the resulting fundamental reverse of the U.S. geopolitical and strategic priorities, have tremendously favored Russia’s international positioning. The great rift that separated western European states and Washington due to the war against Iraq, rein-forced Moscow political clout in Europe on one hand, but on the other the political turmoil in Ukraine in the aftermath of the 2004 elections pointed out the always striking importance of the nowadays so-called forgotten geopolitical boundaries of the Cold War era. Evidently, the fall of Communism in December 1991 and the “End of History” was not equally the end of the “Great Game” for the control of the international geopolitical chessboard.